Antidiabetic activity of Abroma augustum (L.) L.f. and Cajanus cajan (L.) Millsp. extracts benchmarked through phytochemicals, enzyme inhibition and glucose : Antidiabetic activity of Abroma augustum and Cajanus cajan (Indian Journal of Experimental Biology (IJEB), 2026)
The rising global burden of diabetes mellitus and the limitations of conventional therapies necessitate the exploration of safer, effective plant-based alternatives. Although Abroma augustum (L.) L.f. and Cajanus cajan (L.) Millsp. are traditionally used in Nagaland for diabetes management, scientific validation regarding their specific enzyme inhibition mechanisms and safety profiles remains limited. This study systematically evaluated their antidiabetic potential through phytochemical profiling, antioxidant activity, enzyme kinetics, and glucose uptake assays. Quantitative analysis revealed that 80% ethanol extracts were richer in bioactive constituents, particularly phenols and flavonoids, compared to aqueous extracts. Cajanus cajan consistently demonstrated superior antioxidant activity and potent, competitive inhibition of carbohydrate-hydrolyzing enzymes (α-amylase and α-glucosidase) compared to A. augustum. Furthermore, C. cajan exhibited significantly higher glucose uptake (147.75%) in HepG2 cells. Cytotoxicity assessment in VERO cells indicated that while C. cajan (IC50 139.98 µg/mL) was relatively safe, A. augustum (IC50 115.79 µg/mL) possessed higher cytotoxicity. These findings scientifically validate the antidiabetic potential of A. augustum and C. cajan, supporting their traditional use and warranting further investigation for antidiabetic drug development.